Hubungan Antara Adversity Quotient (AQ) dengan Perilaku Seksual Berisiko pada Remaja di Wilayah Jakarta Pusat - Rahmawati, Veronica Yeni; Puspasari, Jehan; Fitria, Dian (Universitas Malahayati, 2023)
ABSTRACT Adolescents are vulnerable to deviant behavior, one of which is risky sexual behavior which has a negative impact on adolescents, their partners and even their families. The causes of risky sexual behavior in adolescents are internal and external factors. In a study conducted to identify the relationship that occurs in Adversity Quotient (AQ) to risky sexual behavior. The research was carried out using a cross sectional research method with a total sampling technique of purposive sampling. Respondents in this study were students of a health institution in Central Jakarta with a total of 123 respondents. As the research results show, there is a significant relationship between the Adversity Quotient (AQ) for risky sexual behavior with a p value of 0.007 (OR=2.8; 95% CI 1.315-6.321). Recommendations for maternity nursing services to improve health promotion in adolescents through the roles and responsibilities of adolescents so that risky sexual behavior can be avoided. Keywords: Adversity Quotient, Risky Sexual Behavior, Adolescents ABSTRAK Usia remaja rentan dengan perilaku menyimpang salah satunya perilaku seksual berisiko yang memiliki dampak negative bagi remaja, pasangannya bahkan keluarganya. Faktor penyebab adanya perilaku seksual berisiko pada remaja dari faktor internal dan juga faktor eksternal. Penelitian ini bertujuan untuk mengidentifikasi keterkaitan adanya hubungan antara Adversity Quotient (AQ) dengan perilaku seksual berisiko. Penelitian ini dilakukan dengan menerapkan metode penelitian cross sectional dengan teknik total sampling jenis purposive sampling. Responden pada penelitian ini adalah mahasiswa salah satu institusi kesehatan di Jakarta Pusat dengan jumlah 123 responden. Hasil dari penelitian ini menunjukkan adanya hubungan yang signifikan antara Adversity Quotient (AQ) dengan perilaku seksual berisiko dengan nilai p value 0,007 (OR=2,8; 95% CI 1,315-6,321). Rekomendasi bagi pelayanan keperawatan maternitas agar meningkatkan promosi kesehatan pada remaja melalui peran dan tanggung jawab remaja supaya dapat terhindar dari perilaku seksual berisiko. Kata Kunci: Adversity Quotient, Perilaku Seksual Berisiko, Remaja